DAMPAK KERUSAKAN LINGKUNGAN EKOSISTEM TERUMBU KARANG - Hermansyah Hermansyah; Fania Febriani (Jurnal Kependudukan dan Pembangunan Lingkungan, 2020)
Coral reef is a complex, unique, and unique ecosystem that occurs by the diversity of biota inhabitants. The relationship between biotic and abiotic components is very close, so that the exploitation of one type of biota can result in changes in the population of other biota. The main causes of damage to coral reefs are mainly caused by natural factors and human factors. This study aims to: (1) assess the damage to coral reef ecosystems (2) to analyze environmental factors that affect the damage to coral reef ecosystems (3) to formulate policies to deal with damage to coral reef ecosystems. The method used is a Literature Review or literature review. The results of this study indicate the impact of environmental damage on marine ecosystems. The damage was caused by disposal of factory waste or household waste at sea, caused by nature including changes in sea air temperature, typhoons, global climate change, earthquakes, volcanic eruptions, predators and diseases.